THE EFFECT OF SALIENCE AND DISPOSITION EFFECT ON STOCK INVESTMENT DECISIONS ON INVESTORS IN SURABAYA - Jessica Ratna Subandi; Sautma Ronni Basana (International Journal of Financial and Investment Studies (IJFIS), 2020)
This study aims to prove the effect of salience and disposition on investors' investment decisions in Surabaya. In addition, this study also seeks to see the effect of salience and disposition effect on investment decisions with the type of investor as a moderating variable. This type of research is quantitative research with associative methods and primary data sources. The data collection technique used a questionnaire. The data that has been collected is then processed using Partial Least Squares (PLS). The results showed that the salience and disposition effect had a significant influence on investment decisions. In addition, the types of investors weaken the relationship between the salience and disposition effect on investment decisions.